Production of Doubled Haploids in cucumber - Elena A. Domblides; Sergey N. Belov; Alexey V. Soldatenko; Victor F. Pivovarov (Овощи России)
Implementation of cell technologies has essentially improved the plant breeding process in agricultural crops in the world. The production of pure lines in cultivated crops, particularly among cross-pollinated species such as cucumber (Cucumis sativus L.) requires much time, labor and expense. Thus, the use of DH-plants for production of fully homozygous lines for one year becomes a very promising method for near cucumber breeding program. The major factor limiting the wide use of DH is a lack of effective protocol for large-scale plant production. In this review the historical facts with description of three main methods of DH-plant production were presented. By now these three methods have been such as parthenogenesis in situ induced by pollination with irradiated or chemically treated pollen; androgenesis in vitro including anther and isolated microspore cultivation in vitro; gynogenesis through ovule cultivation in vitro. Comparative analysis of published data with regard to the efficiency of the technology for DH-plant production was shown as well as advantages and limitations of each technology were described.